Development of resistance to experimental tick (Boophilus microplus) infestations in European breed cattle - Babjee, Shaik Mohamed Amin; Riek, R. F. (Persatuan Doktor Veterinar Malaysia, 1986)
Five Bos taurus calves which had not been previously exposed to the cattle tick Boophilus micro plus were experimentally infested repeatedly for six times with 20,000 B. microplus larvae. Their level of resistance was assessed by the number of engorged ticks produced, the effect on tick weight, the weight of eggs produced and the viability of the eggs. Except for the fourth infestation, all calves develop a significant level of resistance after a primary exposure. On the first infestation the mean yield of engorged female ticks was 39.2% of the larvae applied. The mean yields from the second to the sixth infestation were 8.3%. 10.3%, 11.8%, 6.3% and 4.6% respectively. The level of resistance fluctuated during the course of repeated infestations but the resistance level was reinforced after the individual animal had received a total of 80,000 larvae in the fifth infestation. The engorged tick weights were dropped in subsequent infestation after the primary one but there were no deleterious effects on the egg production and the viability of the eggs.